Risk and protection factors for women’s health in the prevention of cervical cancer - Ana Carolina de Oliveira; Regina Soares Pessoa; Ayla Maria Calixto de Carvalho; Rosilane de Lima Brito Magalhães (Rev Rene)
This study aimed to investigate the risk and protection factors for women who access health services for the realization of preventive screening for cervical cancer. Quantitative study conducted with 51 women in Teresina-PI, Brazil, in August 2013. The semi-structured form caught the variables of interest and the data were analyzed by the SPSS. Of the women, 72.5% were aged 25-39 years, 66.7% were married, and 55.0% accessed the service for prevention. With regard to the risk factors, 41.2% were overweight, 19.6% obese, and 72.5% were sedentary. Regarding the access to health services, 78.5% sought care in the past year. The cervical cancer screening program should be discussed in the sociocultural context, which will promote understanding and adherence to the recommendations of take the exam periodically. For this purpose, we recommend conducting immediate and effective measures to improve the viability of public policies for women’s health.